Pressure and its derivative with respect to piston Mach number for an oscillating cone - Shabana, Ayesha; Monis, Renita; Crasta, Asha; Khan, Sher Afghan (International Organization of Scientific Research ( IOSR ), 2016)
The aim of present study is to obtain mathematical expressions for surface pressure and its derivative with respect to Piston Mach number for an oscillating cone. The effects of Mach number and it’s geometry on Pressure and its derivative with respect to inertia level and incidence angle, and the results have been obtained. The non-dimensional surface pressure distribution on the cone remain linear for lower angle of incidence and Mach number, however, for higher Mach numbers non-linearity creeps in. For higher Mach number due to viscous-inviscid interaction the flow behaves differently. Also, it is observed that there is interaction between the boundary layer and entropy layer and this interaction makes the flow on the surface of the cone very complex. At large Mach numbers the aerodynamic heating will be a serious concern. At high angle theta and low Mach number shock wave will be detached. The surface pressure derivative with Mach number on the cone exhibits linear behaviour for lower Mach number and angle theta and non-linearity for large Mach number and angle theta.